TRANSPARANSI DAN AKUNTABILITAS PELAKSANAAN SERTA PENATAUSAHAAN BELANJA BANTUAN SOSIAL PADA SATUAN KERJA PENGELOLA KEUANGAN DAERAH KABUPATEN SIGI - Anwar M., Nasruddin A.; Ridwan, H.; Yusnita, Nina (Katalogis, 2018)
The purpose of this study are: 1) to determine and describe the transparency and accountability of the management of social assistance expenditure; 2) to identify inhibiting factors in the implementation and administration of social assistance expenditure; 3) to provide altenative solution of the inhibiting factors. The study is descriptive with case study approach. The result shows that: 1) the transparency and accountability of the implementation and administration of social assistance expenditure in the governmental working units Sigi District has not been fully implemented; 2) the inhibiting factors in the management of social assistance expenditure in Sigi District are: the lack of understanding of the mechanism of social assistance expenditure distribution, accountability reports that are not yet in accordance with the provisions, and the lack of human resources both in quantity and quality; 3) activities need to performed are: socialization of social assistance expenditure, to increase and improve the quality of employees, verify and survey the acceptance of social assistance, and revise regulations related to the provision of social assistance.